A new window of opportunity for TAVI - Weich, Hellmuth; van Wyk, Jacques; van Zyl, Wynand; Bapat, Vinayak (SA Heart Journal, 2017)
This short report features the role of multi detector computer tomography (MDCT) in imaging the ascending aorta to assess the feasibility of a transaortic access route for transcatheter placement of an Edwards SAPIEN XTTM aortic valve.